2012
DOI: 10.1002/ps.3353
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of diacylhydrazine insecticides to the predatory bug Orius laevigatus: in vivo and modelling/docking experiments

Abstract: The insect toxicity assays demonstrated that MACs are selective for O. laevigatus. The modelling/docking experiments are indications that these pesticides do not bind with the LBD-EcR of O. laevigatus and support the supposition that they show no biological effects in the predatory bug. These data help in explaining the compatible use of MACs together with predatory bugs in IPM programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
0
9
0
3
Order By: Relevance
“…We used the T. castaneum structure as a template by accounting for its phylogenetic relationship with that suggested in the phylogenetic tree; however, we also modelled the F. auricularia EcR‐LBD based on B. tabaci structure as a control. As previously reported (Soin et al ., 2009; Amor et al ., 2012), different solutions resulted from the docking of tebufenozide to the ecdysone‐binding site of TcEcR‐LBD. A solution that seems to be particularly relevant includes the binding of the ethyl‐phenyl ring (B ring of the DBH) of the agonist in a cavity, which extends the binding site of TcEcR‐LBD to a location that is opposite to the cavity that harbours the alkyl chain of the ecdysteroid (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used the T. castaneum structure as a template by accounting for its phylogenetic relationship with that suggested in the phylogenetic tree; however, we also modelled the F. auricularia EcR‐LBD based on B. tabaci structure as a control. As previously reported (Soin et al ., 2009; Amor et al ., 2012), different solutions resulted from the docking of tebufenozide to the ecdysone‐binding site of TcEcR‐LBD. A solution that seems to be particularly relevant includes the binding of the ethyl‐phenyl ring (B ring of the DBH) of the agonist in a cavity, which extends the binding site of TcEcR‐LBD to a location that is opposite to the cavity that harbours the alkyl chain of the ecdysteroid (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Toxicity assays exposing Insidious flower bug to molt-accelerating compounds, including methoxyfenozide and tebufenozide, showed that this Hemiptera insect is insensitive to these types of chemicals (Amor et al, 2012). Exposure methoxyfenozide or tebufenozide did not cause decreased survival or sublethal effects on reproductive parameters (Amor et al, 2012).…”
Section: Level 3: Individual Amino Acid Residue Comparisonmentioning
confidence: 98%
“…Diacylhydrazines, including methoxyfenozide, were discovered in the 1980s, followed by the commercial analog, tebufenozide (Carlson et al, 2001 Diacylhydrazine (DAH) and bisacylhydrazine (BAH) chemicals (e.g., methoxyfenozide and tebufenozide, respectively), also known as molt-accelerating compounds, act as nonsteroidal agonists of the ecdysteroid receptor (EcR) (Amor et al, 2012). Molting is a necessary process for normal growth and development in insects and other invertebrates.…”
Section: Case Example 1: Susceptibility Of Beneficial Insects To Moltmentioning
confidence: 99%
See 2 more Smart Citations